Analysis of Factors Affecting Interest in Using Digital Payment Methods in E-wallet in Denpasar City - I Wayan Eka Arimbawa; AA's Istri Ita Paramitha; Ni Made Estiyanti (Budapest International Research and Critics University, 2022)
This research was conducted to obtain the results of the factors that affect a person's interest in using the LinkAja e-wallet, especially in the Denpasar city area, using the TAM (Technology Acceptance Model) model. This study used three main variables from TAM and four additional variables from previous studies' results. In this study, data were obtained directly from parties related to distributing questionnaires, for the number of samples used were 120 respondents using the area sampling technique. In this area sampling technique, 120 samples were divided based on four areas in the city of Denpasar. Thus, the sample used for each area was 30. The data obtained were analyzed using the Partial Least Square (PLS) method using smartPLS software. The results of the tests carried out indicate that the accepted hypothesis is the computer self-efficacy variable on the perceived usefulness and perceived easy of use variables, the culture variable on perceived usefulness, the perceived security variable on trust, the perceived usefulness variable on attitude toward using, the perceived ease of use variable on perceived usefulness and attitude toward using, attitude toward using a variable on behavioural intention to use the variable, trust variable on behavioural intention to use the variable. Then there are also the results of the rejected hypothesis with a positive but not significant effect on the interest in using the LinkAja e-wallet, namely the culture variable on the perceived usefulness variable.